A STUDY OF PREVALENCE RATE AND PREDISPOSING FACTORS OF GALL STONES IN SARABURI HOSPITAL PERSONNEL - MUKDEEPROM1, Panida (The ASEAN Journal of Radiology, 2023)
This paper reports the prevalence rate and possible risk factors of gall stone in Saraburi hospital personnel. 400 Cases were randomly selected for ultrasonographic examination of the abdomen. There were 64 men (16%) and 336 women (84%). Gall stones were found in 18 cases (4.5%). The prevalence is 1.6% in men(1 in 64 cases) and 5.1% in women (17 in 336 cases). The predisposing factors for gall stones are aging and increasing number of parity. Although there is more tendency for women and obese person to have gall stones according to this study but there is no statistical significant increased prevalence of gall stones in these two groups.